T-type calcium channels: From molecule to therapeutic opportunities - Weiss, Norbert; Zamponi, Gerald W (The international journal of biochemistry & cell biology, 2019)
T-type calcium channels serve an essential role in the functioning of the nervous system. They exhibit unique properties among voltage-gated calcium channels, and mediate specific roles in brain function. Over the recent years, it has come to light that a number of chronic neurological disorders arise from defects in T-type channel function. The question then arises as to whether T-type channels could represent a relevant druggable target. In this review, we introduce the diversity, molecular structure, and principal electrophysiological properties of T-type channels. Then, we highlight their role in neuronal development, and their pathophysiological role in the nervous system. Finally, we discuss the potential of T-type channels as therapeutic targets in light of recent advances in their pharmacopoeia.
Keywords: Calcium; Protein Transport; transport proteinů; Humans; zvířata; Neuron; Calcium Channels, T-Type; vápníkové kanály - typ T; Neurons; sekvence aminokyselin; Ca(v)3 channel; Epilepsy; T-type channel; Animals; Amino Acid Sequence; lidé; nemoci nervového systému; neurony; Nervous System Diseases; Pain